Lean Body Mass and Anaerobic Performance in Children and Adolescents - Correas-Gómez, Lorena (UMA Editorial, 2017)
The acquisition of lean body mass (LBM) during childhood and adolescence must be a main concern to ensure motor development and healthy growth. Participation in regular physical activity programs during the growth period plays a positive role in bone and lean mass accrual in addition to diverse health-derived benefits but there is need to consider account for biological maturity and body size. Methodologies to predict skeletal muscle mass (SMM) or fat-free mass (FFM) are not error-free. Thus, the relationship between performance and muscularity may be affected. The analysis of the associations between known models to estimate LBM with anaerobic performance (strength) should be pertinent to evaluate construct validity. The relationship between strength and muscle size has been extensively explored in adults but less is known in adolescents. Furthermore, hydration has been barely associated with anaerobic performance. This is a paradoxical situation because the child is mainly involved in high intensity and short duration exercises in most daily tasks, spontaneous physical activity or sports. Three different studies were carried out in a sample of children, adolescents, and young adults.
Indicadores de masa muscular esquelética y rendimiento araeróbico en niños y adolescentes
Study 1. Objective. To provide reference data of regional and total SMM and FFM derived from anthropometry among age, sex and sport participation groups for healthy Caucasian children and adolescents, accounting for body size and maturation. Study design. Cross-sectional data of 1438 participants aged 8-18y. FFM and SMM were estimated from anthropometric variables. General linear model of mixed factors was used to analyze variance of FFM or SMM across groups and confounders. Ln-ln regression analysis was applied to describe SMM scaling associations with height. Results. Only active boys increased significantly their regional muscularity from primary to secondary school (arm, ∆0.78cm; thigh, ∆1.44cm; calf, ∆1.16cm) and from secondary to high school (arm, ∆2.81cm; thigh, ∆2.51cm; calf, ∆1.88cm; all P<0.0001). Conclusions. Our findings showed sex differences in the relationship between total and regional SMM and age. A novel contribution was that sport practice may affect SMM accrual after puberty, and growth of regional muscle-to-height ratio before PHV. Study 2. Objectives. To analyze the validity and agreement between laboratory and field methods to estimate FFM and SMM in children, adolescents, and young adults. And, to explore construct validity. Study design. Validation studies were designed using a large dataset of children and adolescents aged 6-21y. Body composition was assessed by isotope dilution method, dual-energy X-ray absorptiometry (DXA), bioelectrical impedance analysis (BIA) and anthropometry (ANT). Static and dynamic strength were tested. Concurrent validity was analyzed by differences between methods and concordance coefficient correlation; agreement by Bland-Altman, and construct validity by correlations between muscle and strength. Results. A total of 531 measures were analyzed (287 boys). FFM measures from alternative techniques underestimated FFM measures from deuterium dilution. Isometric strength correlated better with lean and muscle mass variables than explosive dynamic tests. Conclusions. The results did not confirm agreement between methods. There was not a perfect method for all situations. The results evidence the need for developing specific models to estimate FFM and SMM in physically active prepubertal and pubertal youth. Study 3. Objective. To explore the associations and predictive capacity of regional SMM in isometric strength, and water distribution in dynamic strength. Study design. 1) Intracellular water (ICW) and Sprint Performance in 158 adolescents aged 12-18y (15.0 ± 1.5y). 2) Regional SMM and Lower Limb Strength (LLS) in 166 healthy adolescents aged 12-18y. Best performance out of two measures of 30m-sprint and LLS was selected. Athletes were identified with ad hoc questionnaires. The best-correlated variables were included in a stepwise regression analysis. Results. 1) SMM (kg), the athlete condition and %ICW were identified as predictors of speed in 30m (P<0.001, R2 = 0.620). 2) Similar results were found for a model including SMM (kg), athlete condition, and height (R2 = 0.488, P<0.001) and for an alternative model including CCG, athlete condition, sex and height (R2 = 0.484, P<0.001). Conclusions. One of the main findings was that ICW assessed by bioimpedance analysis was a significant predictor of sprint performance in adolescents. And, that, a simple measure like corrected calf girth was found to contribute significantly for estimating lower limb strength almost as much as whole lean body mass.
Keywords: Ejercicio físico - Aspectos fisiológicos - Tesis doctorales; Fisiología del ejercicio; Desarrollo somático; Pediatría; Composición del cuerpo